ADR Effects on Domestic Latin American Financial Market - Mendiola, Alfredo (2010)
The purpose of this paper is to revisit and extend previous research work that examines the ADR-listing effects on the trading process of all the domestically-listed stocks in the main Latin American exchanges. The most important result is consistent with the idea of a greater isolation (from global markets) of the singly-listed stocks in the post-cross-listing period. These results persist over the cross-listing months. As expected, the cross-listed stocks become more integrated in the post-cross listing period